A brief review on mass/optical spectrometry for imaging analysis of biological samples. Issue 1 (2nd January 2019) - Xu, Xinrong; Zhong, Jingjun; Su, Yingying; Zou, Zhirong; He, Yaqin; Hou, Xiandeng
Abstract: Imaging analysis, especially bioimaging analysis, has been a hot research topic in recent years. There are numerous imaging analysis techniques for diverse applications of a wide spectrum of samples, with their unique advantages and disadvantages, and there are several related reviews published yearly. Among them, imaging mass spectrometry (IMS) is a relatively novel analytical technique for studying the distribution of molecular or ionic species at the level of tissue, cell, or subcellular, with its main feature of combining mass spectra for molecular identification and image visualization for quick and convenient analysis. The IMS does not require chemical labeling or complex sample preparation. This review, therefore, mainly focuses on the popular emerging IMS technique, including related ionization techniques in connection with their IMS applications, and some unique optical imaging techniques such as chemiluminescence imaging and dual-modal bioimaging for biological sample analysis, with 105 related recent references.